2006
DOI: 10.1577/t05-031.1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Fish Assemblage Structure Upstream of Impoundments within the Upper Wabash River Basin, Indiana

Abstract: The effects of dams and impoundments on downstream fish assemblages have been well documented, but changes in fish assemblages in upstream tributaries have received little attention. We compared changes in abundance and composition in fish assemblages in streams fragmented by impoundments with those found in nearby unfragmented streams by sampling fish, in‐stream habitat, physicochemical factors, and drainage features in 22 agriculturally dominated streams during the summers of 2002 and 2003. Eleven sampling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
68
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 39 publications
7
68
0
Order By: Relevance
“…Moreover, sedimentation has been attributed to the reduction in trophic diversity in fish assemblages in Midwestern lotic systems (Berkman and Rabeni, 1987). The findings of our study agree with Berkman and Rabeni (1987) and others (e.g., Karr et al, 1985;Guenther and Spacie, 2006;Palić et al, 2007;Gido et al, 2010) where specialized invertivorous and herbivorous fishes declined in altered fluvial environments and were replaced by habitat generalists with piscivorous, planktivorous, or omnivorous feeding strategies (e.g., habitat generalist and facultative reservoir species; Karr et al, 1985;Falke and Gido, 2006). Although our results indicate that certain groups of species have expanded, possible temporal increases in gear efficiency have occurred and influenced our results.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, sedimentation has been attributed to the reduction in trophic diversity in fish assemblages in Midwestern lotic systems (Berkman and Rabeni, 1987). The findings of our study agree with Berkman and Rabeni (1987) and others (e.g., Karr et al, 1985;Guenther and Spacie, 2006;Palić et al, 2007;Gido et al, 2010) where specialized invertivorous and herbivorous fishes declined in altered fluvial environments and were replaced by habitat generalists with piscivorous, planktivorous, or omnivorous feeding strategies (e.g., habitat generalist and facultative reservoir species; Karr et al, 1985;Falke and Gido, 2006). Although our results indicate that certain groups of species have expanded, possible temporal increases in gear efficiency have occurred and influenced our results.…”
Section: Discussionsupporting
confidence: 94%
“…The reduction of flowing water and the accumulation of fine sediments potentially explain the decline of fluvial fishes with lithophilic spawning strategies. Similarly, Guenther and Spacie (2006) observed declines of lithophilic spawners due to sedimentation upstream of impoundments in the Wabash River. Increased sedimentation considerably alters the trophic structure of local fish assemblages in many Midwestern lotic systems with hydrologic disturbance (Menzel, 1981(Menzel, , 1983Poff and Allan, 1995).…”
Section: Discussionmentioning
confidence: 79%
“…Considerable attention has been given to the impacts on fish assemblages of downstream reaches (De Jalon et al 1994;Quinn and Kwak 2003;Merona et al 2005) and upstream reaches (Gido et al 2000;Quist et al 2005;Guenther and Spacie 2006). Remarkable changes in fish assemblages have been found after the impoundment of reservoirs.…”
mentioning
confidence: 99%
“…We found that the grass pickerel was a top carnivore (piscivore) within these Indiana ecosystems, which is similar to Guenther and Spacie (2006). Top carnivore presence in an ecosystem is an important factor in evaluating fish communities and can be used in fisheries management to evaluate the overall health of the ecosystem.…”
Section: Discussionmentioning
confidence: 57%
“…As the quality of a stream declines, top carnivore populations decline and disappear (Karr 1981). For example, Guenther and Spacie (2006) found increased redfin pickerel (= grass pickerel) in streams that were not associated with downstream reservoirs. The northern pike is thought to structure fish communities primarily through predation (Paukert and Willis 2003), and this scenario could be applied to the grass pickerel in Indiana.…”
Section: Discussionmentioning
confidence: 99%